The importance of speed abilities for a football player (Fiep Bulletin - online, 2013)
Pavel Nedv?d, the football player of 2003, Juventus Torino: “Football is increasingly faster. In order to win a match, one has to outrun and surprise the rival. The future in football belongs to players, who are very fast and the ball does not make them problems.” Constantly increasing demands on individual speed abilities of players as well as on speed of collaboration (cooperation) of players can unambiguously be considered one of the main characteristics of the contemporary professional football. Football is played very fast on the international forum. It is played in a simple way – two touches with all players in constant movement. The game has incredibly sped up; it has become more aggressive and more demanding regarding physical condition. The worldwide developmental tendency in football is the increase in dynamics of the game, which in turn increases requirements on speed abilities of players during matches. The 2002 FIFA World Cup in South Korea and Japan is a clear proof of this. Individual expressions of speed abilities of many great football players were on high level and were dominated by the speed of controlling the ball in individual penetrations. Mainly the game style of South Korea and China had an extraordinary acceptance in this sense.